Treatment of Hepatitis C Virus Infection - Khan, Mobin; Azam, Md Golam (Journal of Bangladesh College of Physicians and Surgeons, 2010)
DOI: 10.3329/jbcps.v26i1.4225 J Bangladesh Coll Phys Surg 2008; 26: 1-2